Administrative Model for Quality Assurance in a Maritime Institution: Response to Globalization - Alimen, Rolando A. (JPAIR Multidisciplinary Research, 2009)
In response to the changing demands of globalization, this study developed an administrative model for quality assurance intended in a maritime institution and to determine the perceived levels of institutional domains and the impact of accreditation as influenced by respondent-related factors. This research employed a quantitative-qualitative mode of data collection. Stratified proportionate random sampling method was used in the selection of the final participants of this study, specifically the internal and external respondents. Results of the study showed the "very effective" and "very influential" perception levels of the following variables: institutional domains and impact of accreditation. The SWOT analysis and Swanson’s Systems Model for Performance Improvement was utilized and yielded significant factors leading to the formulation of the administrative model.